Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-73133-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of a Dynamic Social Network Built from PGP Keyrings

Abstract: Abstract. Social networks are the focus of a large body of research. A number of popular email encryption tools make use of online directories to store public key information. These can be used to build a social network of people connected by email relationships. Since these directories contain creation and expiration time-stamps, the corresponding network can be built and analysed dynamically. At any given point, a snapshot of the current state of the model can be observed and traditional metrics evaluated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Within it, a 'small-world phenomenon' characterized by short trust path lengths could be detected (̌apkun, Buttyan, Hubaux, 2002;Ulrich et al 2011). Warren, Wilkinson and Warnecke (2007) found that the overall connectivity of the web of trust increased over time, while social distance between subgroups slightly decreased. hese changes can be traced back to real life events where people can sign each other's keys, such as Linux conferences.…”
Section: Related Workmentioning
confidence: 99%
“…Within it, a 'small-world phenomenon' characterized by short trust path lengths could be detected (̌apkun, Buttyan, Hubaux, 2002;Ulrich et al 2011). Warren, Wilkinson and Warnecke (2007) found that the overall connectivity of the web of trust increased over time, while social distance between subgroups slightly decreased. hese changes can be traced back to real life events where people can sign each other's keys, such as Linux conferences.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the observation in social networks that neighbours more likely seem to have the same attributes/attitudes [7] the agreement of a neighbour to a function seems to be more important than a simple forward. There exists both research on information spreading in models of social networks that usually make assumptions on uniformly distributed probabilities in certain areas of a social network depending on its structure and on the evaluation of actual information spreading in existing social networks like the one built by GPG keys [14] or Flickr [9].…”
Section: Fulfilment Of Security Requirementsmentioning
confidence: 99%